Automated design of local search algorithms: Predicting algorithmic components with LSTM - Meng, Weiyao; Qu, Rong (Expert systems with applications, 2024)
With a recently defined AutoGCOP framework, the design of local search algorithms has been defined as the composition of elementary algorithmic components. The effective compositions of the best algorithms thus retain useful knowledge of effective algorithm design. This paper investigates machine learning to learn and extract useful knowledge in effective algorithmic compositions. The process of forecasting algorithmic components in the design of effective local search algorithms is defined as a sequence classification task, and solved by a long short-term memory (LSTM) neural network to systematically analyse algorithmic compositions. Compared with other learning models, the results reveal the superior prediction performance of the proposed LSTM. Further analysis identifies some key features of algorithmic compositions and confirms their effectiveness for improving the prediction, thus supporting effective automated algorithm design. •The design of local search algorithms is defined as a sequence classification task.•LSTM is applied to forecast algorithmic components for automated composition.•LSTM has a better classification performance as compared with other classifiers.•Key features for sequence classification are identified to support algorithm design.